Bindning av PFAS-ämnen till humus- och fulvosyror : en dialysstudie - Kikuchi, Johannes (SLU/Dept. of Soil and Environment, 2020)
To make more accurate predictions of the mobility of perfluoroalkyl substances (PFAS) in soil and water, better understanding of PFAS sorption to components of the terrestrial and aquatic systems is needed. This study investigated the possible sorption of a range of PFAS compounds with varying chemistries to humic acid (HA) and fulvic acid (FA) using a dialysis bag experimental set-up. No sorption of any of the analysed compounds was observed to either fractions of dissolved organic matter (DOM) using this experimental set-up. Our findings suggest that soil water containing fulvic acid does not enhance the solubility of PFAS compounds and is thus not likely to act as a transport vector for these compounds in natural systems. The non-binding of PFAS-compounds to the, in natural systems, solid phase humic acid suggest that PFAS-mobility and retainment in soil due to interaction with organic matter is more likely mediated by the lesser charged and more hydrophobic humin fraction.